2020
DOI: 10.1080/17441692.2020.1775867
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent mothers affected by HIV and their children: A scoping review of evidence and experiences from sub-Saharan Africa

Abstract: While adolescents have received increasing attention in the global HIV response and international strategies and commitments, adolescent mothers and their children remain largely overlooked in research, funding and, programming for health-related outcomes. We conducted an extensive scoping review of current evidence on the experiences of adolescent mothers affected by HIV and their children in this region. We included published literature and conference abstracts, complemented by consultations with key stakeho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 62 publications
2
56
0
Order By: Relevance
“…Safe conception considerationsplanned pregnancies that coincide with viral suppression, but also socio-emotional readinessmust be integrated in HIV and SRH service provision for adolescent girls and young women living with HIV. It is also critical to shift away from a risk-centred narrative, promoting more nuanced evidence on young women's sexual and reproductive health needs and practices, especially among ALHIV [15,30,41]. Additional research is needed to understand which factors support adolescent girls and young women to use dual protection and have well-timed, supported pregnancies, particularly in the context of HIV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Safe conception considerationsplanned pregnancies that coincide with viral suppression, but also socio-emotional readinessmust be integrated in HIV and SRH service provision for adolescent girls and young women living with HIV. It is also critical to shift away from a risk-centred narrative, promoting more nuanced evidence on young women's sexual and reproductive health needs and practices, especially among ALHIV [15,30,41]. Additional research is needed to understand which factors support adolescent girls and young women to use dual protection and have well-timed, supported pregnancies, particularly in the context of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…All the rates reported below are adjusted predicted probabilities of each outcome being reported, holding age, informal housing and poverty at their mean values. Independent of HIV status, adolescent mothers were less likely to report wanting >2 children (aOR 0.57, CI 0.43 to 0.75), possibly due to the challenges already experienced [30]. Predicted probabilitiesadjusted to take into account age, informal housing and povertyshowed that aspirations for two or more children were lowest among AMLHIV (62.9%) and highest among nulliparous controls (77.4%).…”
Section: Effect Of Hiv and Motherhood On Reproductive Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, for pregnant adolescents living with HIV, additional considerations may arise; poor mental health may have impacts on service engagement (HIV, sexual and reproductive health, antenatal) and onwards HIV transmission (i.e. prevention of mother to child transmission)-concerns critical to both adolescent and child wellbeing [89]. Adolescents living with HIV (both mothers and fathers) and their children may have specific needs, and therefore, further investigations into the mental health needs of this group are required to bolster positive outcomes for this group.…”
Section: Adolescent Pregnancy Hiv and Mental Health: A Critical Evidence Gapmentioning
confidence: 99%
“…Nevertheless, there is limited information about the interactions of the three conditions and their concomitant impact on maternal health [ 11 , 21 ]. Of note, a recent scoping review about the experiences of adolescent mothers living with HIV in SSA, concluded that information about pregnancy and perinatal outcomes of this population group was almost non-existent [ 22 ].…”
Section: Introductionmentioning
confidence: 99%